Staattiset koodimetriikat ja niiden yhteys muutoksen määrään TIMissä - Kauko, Ilari (2023)
Static code metrics are ways to measure software code without executing it. Typically, they are used to evaluate code quality, such as understandability and maintainabiliy, but their applicability to it is somewhat questionable. The topic has been under research for about 50 years without univocal results. Software industry uses them quite steadily to validate code, but academic research about them has given rather contradictory results. The source code of TIM, an educational web application developed in the University of Jyväskylä, was researched by the available metric tools and it turned out that their relation to the amount of Git commits in the Git log was remarkable. However, the metrics the research emphasized were somewhat different from what previous research has emphasized, which may tell about the programming paradigm used in TIM.